Proceedings of 6th Electronics Packaging Technology Conference (EPTC 2004) (IEEE Cat. No.04EX971)
DOI: 10.1109/eptc.2004.1396676
|View full text |Cite
|
Sign up to set email alerts
|

Package optimization of a stacked die flip chip based test package

Abstract: We report a case study for the optimization of a flip chip based stacked die array test package. We demonstrate the importance of package substrate design and substrate thickness on the processibility and package warpage control. We found that for thin substrates copper balancing of the top and bottom die is crucial. We show the impact of flip chip die thickness and substrate thickness on the die attach of the top die(s) in the stack. Investigations on different top die attach alternatives show that tape die a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…However within a chip stack warpage requires much tighter control in order to avoid failures. For a flip chip/wirebond stack Pohl et al [6] investigated the factors, which influence the warpage and reliability of the construction. They found that material physics, which includes stress, adhesion, and reliability aspects, must be understood.…”
Section: Second Level Reliability Implicationsmentioning
confidence: 99%
“…However within a chip stack warpage requires much tighter control in order to avoid failures. For a flip chip/wirebond stack Pohl et al [6] investigated the factors, which influence the warpage and reliability of the construction. They found that material physics, which includes stress, adhesion, and reliability aspects, must be understood.…”
Section: Second Level Reliability Implicationsmentioning
confidence: 99%